2021
DOI: 10.22460/project.v4i1.p134-138
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Deixis of Song Lyrics in Adele Entitled All I Ask

Abstract: The title of this research is analyzing the Deixis of Song Lyrics in Adele entitled “All I Ask”. The researchers used a descriptive qualitative method in this research. This research are aimed to find out the types of deixis (Personal, Spatial, and Temporal) and the most dominant deixis which found in the lyrics of Adele's song. Based on the results and discussion, the researchers concluded that all deixis which proposed by Yule are found in Adele’s song lyrics. Personal deixis is mostly found in 38 occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
0
0
1
Order By: Relevance
“…Salah satu kajian yang termasuk ke dalam pragmatik adalah deiksis. Deiksis berasal dari bahasa Yunani deiktikos yang berarti penunjukan secara langsung (Haloho & Johan, 2020;Salamudin & Efransyah, 2021;Saputra & Apsari, 2021;Tanaka, 2011). Dalam hal ini, deiksis berarti kata atau leksem yang memiliki referen berubah-ubah sesuai dengan tempat, waktu, bahkan situasi pada saat tuturan tersebut disampaikan (Yule, 1996).…”
Section: Pendahuluanunclassified
“…Salah satu kajian yang termasuk ke dalam pragmatik adalah deiksis. Deiksis berasal dari bahasa Yunani deiktikos yang berarti penunjukan secara langsung (Haloho & Johan, 2020;Salamudin & Efransyah, 2021;Saputra & Apsari, 2021;Tanaka, 2011). Dalam hal ini, deiksis berarti kata atau leksem yang memiliki referen berubah-ubah sesuai dengan tempat, waktu, bahkan situasi pada saat tuturan tersebut disampaikan (Yule, 1996).…”
Section: Pendahuluanunclassified
“…Although a lot of previous studies have been found in papers, most of them focus on song lyrics (Aryawan et al, 2022;Rokhmah & Santoso, 2022, Salamudin & Efransyah, 2021Sinaga et al, 2020), film (Dion Ari Saputra et al, 2022;Hidayat et al, 2021), and talk show (Putri et al, 2022), to mention a few. Although deixis was also studied in talk show, the data were not taken from Ellen Guneres.…”
Section: Introductionmentioning
confidence: 99%